THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT ON EMPLOYEE LOYALTY WHICH AN IMPACT ON THE PERFORMANCE OF EMPLOYEES OF PT PATRIA MARITIM PERKASA (PMP) BATAM - Kusuma, Andhi; Indrayani, Indrayani; Satriawan, Bambang; Wibisono, Chablullah (RADJA PUBLIKA, 2022)
The cause of this research is to understand the affect of organizational culture and work environment towards the loyalty of personnel in addition to their impact at the performance of employees of PT. Patria Maritim Perkasa Batam. approach of statistics collection on this observe is a questionnaire, remark, documentation. strategies of descriptive and quantitative techniques with course evaluation that may be used to measure the affect of organizational culture and work surroundings towards the loyalty of employees as well as their effect at the overall performance of employees of PT Patria Maritim Perkasa Batam. based totally on a take a look at of the free variable F (organizational culture, work environment) mutually have a fantastic and huge impact against the variable is certain ( the loyalty of personnel and employee performance).